Dietary vs. light stimulated smoltification: effects on smolt development and appetite regulation in pre- and post- smolts - Jansen, Melissa (UiT Norges arktiske universitet, 2020)
The transfer of smolt from freshwater (FW) to seawater (SW) is a critical stage in the farming of Atlantic salmon (Salmo salar) with mortalities of up to 15 % after transfer. One of the reasons for this loss is suboptimal smolt quality. It is therefore important to ensure that the fish are fully SW adapted before transfer to SW. Traditionally, smoltification is stimulated by exposing the fish to a light regime mimicking a natural summer- winter- spring daylength signal (light treatment). In recent years, it has become more and more common to keep the fish at continuous light throughout the FW phase and feeding them a specialized feed supplemented with a salt mixture and in some cases, also with a free tryptophan supplement, during the last weeks prior to SW transfer (dietary stimulation). However, it has not been shown whether the dietary approach triggers a true smoltification and stimulate all the mechanisms needed for optimal growth and welfare in SW. In the present study, we compared smolt development and SW growth performance between the traditional light treatment and a group that received a commercial smoltification feed containing an ion mix and free tryptophan. In addition, we investigated changes in appetite regulators in response to smoltification and treatment given. With regard to smoltification during the FW phase, we found that both treatment groups were changing skin color, but only the light treated group (those subjected to a short photoperiod (SP) 9L:15D) had a reduction in condition factor (K) indicating that a true smoltification took place only in this group. In contrast, the dietary treated group showed a higher gain in body mass and better SW tolerance throughout the FW phase. Both treatment groups had similar specific growth rate (SGR) during the SW phase, indicating that feed supplemented with a salt mixture and free tryptophan is a good alternative to the traditional light treatment. Some changes were seen in appetite regulators that could be a response to smoltification and treatment ...